Characterisation of Hot Days and Heatwaves: A Case Study for Queensland State in Australia - U Laz, Orpita; Rahman, Ataur (International Journal of Integrated Engineering, 2022)
Due to climate change, the temperature is increasing; however, its spatial and temporal distribution and trend are less understood. To fill this research gap, this study examines the nature of temperature rise in the Queensland State of Australia. Based on the daily maximum and minimum temperature data of 17 weather stations covering 1969-2018, the geographical patterns as well as the temporal variations of hot days and heatwaves over the state are examined. The Mann-Kendall trend test and simple regression methods are employed for detecting trends. The majority of the stations show a significant increase in temperature indices, indicating the warming of the state. Out of 17 stations, 12/14 display a significant increase in the annual frequency of warm days/nights, and 2/11 reveal a significant decrease in the frequency of cool days/nights. The rest of the stations show no change, except two stations showing an upward trend for cold nights. The Excess Heat Factor (EHF) index is used to identify the heat waves. Over Southern Queensland, frequency, total duration, and maximum duration of heatwaves are found to have increased significantly with a greater magnitude compared to other parts of the state. These findings will be useful for climate adaption and mitigation measures in Queensland is compulsory.